The Effect of Forensic Accounting and Investigative Auditing on Fraud Prevention and Disclosure, with Internal Control System Effectiveness as a Moderating Variable - Ayu Ningtyas Dwi Prasasti; Fatchan Achyani (SAINTIS Publishing, 2025)
This study aims to examine the effect of forensic accounting and investigative auditing on fraud prevention and detection, with the effectiveness of internal control systems as a moderating variable at the Financial and Development Supervisory Agency (BPKP) of Central Java Province. This study uses a quantitative approach. The population in this study consisted of BPKP auditors in Central Java Province, with a total of 60 respondents selected using purposive sampling. The data used in this study was primary data collected by distributing questionnaires. Data analysis used the Structural Equation Modeling (SEM) method through the Partial Least Square (PLS) and Moderated Regression Analysis (MRA) approaches with the SmartPLS Version 4 software application. The results showed that forensic accounting had no effect on fraud prevention and detection, while investigative auditing had a positive and significant effect. The effectiveness of internal control systems was unable to moderate the influence of forensic accounting and investigative auditing on fraud prevention and detection.